National Institute of Standard Technology Approach for Steganography Detection on WhatsApp Audio Files - Abdul Haris Muhammad; Gamaria Mandar (Universitas Ahmad Dahlan, 2024)
Audio steganography in instant messaging applications such as WhatsApp poses new challenges in the field of digital security, especially due to the ability to hide data in frequently used formats. This research examines the effectiveness of steganography detection on WhatsApp audio files by applying a method developed by the National Institute of Standards and Technology (NIST). This approach was chosen due to its reputation in security testing standards, but its use in the context of audio steganography on instant messaging platforms has not been widely explored. The novelty of this research lies in the adaptation of the NIST method specifically for audio steganography analysis in WhatsApp, which includes testing against various compression and end-to-end encryption scenarios. The main findings of this research show that the NIST method successfully improves the accuracy of hidden message detection compared to conventional steganalysis techniques, especially under the condition of compressed audio files. In addition, this research also found that the integration of the NIST method enables more effective detection of steganographic data in encrypted audio files. These results confirm that the NIST method can be successfully adapted for instant messaging applications such as WhatsApp, making a significant contribution in the improvement of digital security. This research not only identifies weaknesses in existing steganography techniques, but also introduces a new framework for more accurate and efficient detection in encrypted environments.